Age-associated changes of transposable elements activity in the oocytes and differences in their content across mammalian genomes. - Bădici, Marco Constantin (Jihočeská univerzita, 2021)
Analysis of expression and DNA methylation of retrotransposons in single oocyte datasets from reproductive young and aged mouse females with the aim to assess the association between aging and altered activity of retrotransposons. Estimation of genomic transposon content in selected mammalian species using genome assembly-independent approach.
Age-associated changes of transposable elements activity in the oocytes and differences in their content across mammalian genomes.
Keywords: nmr; naked mole rat; transposon; retrotransposon; repeat explorer; oocyte; methylation; expression; nmr; naked mole rat; transposon; retrotransposon; repeat explorer; oocyte; methylation; expression